1999
DOI: 10.2337/diacare.22.12.2018
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychobehavioral model of severe hypoglycemia. II. Understanding the risk of severe hypoglycemia.

Abstract: Patients with a history of severe hypoglycemia differed on five of the seven steps of the biopsychobehavioral model of severe hypoglycemia. Helping patients with a recent history of severe hypoglycemia to reduce the frequency of their low-BG events, become more sensitive to early signs of neuroglycopenia and neurogenic symptoms, better recognize occurrence of low BG, and use fast-acting glucose more frequently in the treatment of low BG, may reduce occurrence of future severe hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Exploratory analyses of individual differences for both type 1 diabetes studies indicated a mild relationship between greater routine exposures to hyperglycemia, as reflected by the percentage of SMBG readings Ͼ15 mmol/l, HbA 1c , and more cognitive tests affected by hyperglycemia. This is consistent with the results of studies demonstrating that greater exposure to hypoglycemia is associated with greater cognitive impairments during hypoglycemia (16) and is inconsistent with adaptive theories speculating that individuals may accommodate to extreme blood glucose levels.…”
Section: Individual Effects Of Hyperglycemiasupporting
confidence: 73%
See 1 more Smart Citation
“…Exploratory analyses of individual differences for both type 1 diabetes studies indicated a mild relationship between greater routine exposures to hyperglycemia, as reflected by the percentage of SMBG readings Ͼ15 mmol/l, HbA 1c , and more cognitive tests affected by hyperglycemia. This is consistent with the results of studies demonstrating that greater exposure to hypoglycemia is associated with greater cognitive impairments during hypoglycemia (16) and is inconsistent with adaptive theories speculating that individuals may accommodate to extreme blood glucose levels.…”
Section: Individual Effects Of Hyperglycemiasupporting
confidence: 73%
“…Third, the blood glucose readings entered into the HHC were compared with memory meter data to ensure accuracy of the SMBG results. We have used these procedures extensively in our investigations of hypoglycemia (12,16,17).…”
Section: Study 1 Subjectsmentioning
confidence: 99%
“…However, this is a complex process involving several steps, some of which are probably enhanced by education and mental preparation (12). One factor of great importance is how rapidly and to what degree cognitive dysfunction develops during hypoglycemia.…”
Section: Ethicsmentioning
confidence: 99%
“…During events of severe hypoglycemia, insulin-treated patients suffer from cerebral glucose deficiency. The capacity to maintain cognitive function during hypoglycemia is a crucial link in a complex chain of prerequisites to ensure that severe hypoglycemia is prevented by appropriate treatment of the initial hypoglycemia (12).…”
mentioning
confidence: 99%
“…Education should include paying attention to the risks of high daily amounts of insulin. Pregestational educational intervention, e.g., with BG awareness training (BGAT) programs (29), may be helpful to reduce the high risk of SH associated with type 1 diabetic pregnancy.…”
Section: Sequelae Of Shmentioning
confidence: 99%